2020
DOI: 10.1002/lary.29085
|View full text |Cite
|
Sign up to set email alerts
|

Differing Progression to Posterior Glottic Stenosis in Autoimmune and Idiopathic Subglottic Stenosis

Abstract: Objectives/Hypothesis: We sought to characterize rates of progression to posterior glottic stenosis (PGS) from autoimmune or idiopathic subglottic stenosis.Study Design: This was a retrospective review. Methods: Patients from a tertiary-care laryngology practice over a 10-year period with autoimmune or idiopathic subglottic stenosis (SGS) were included. Patients with a history of prolonged intubation or other causes of iatrogenic stenosis were excluded. PGS was confirmed on videostrobolaryngoscopy recordings b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 27 publications
0
10
2
Order By: Relevance
“…Outside of airway surgery, glottic stenosis does not appear to be common in the natural history of iSGS. Dion et al demonstrated that although 31.3% of a group of patients with an autoimmune etiology underlying their subglottic stenosis demonstrated concurrent posterior glottic stenosis, only one case of concurrent glottic stenosis was noted out of 45 (2.2%) patients with iSGS 9 . Our LWEP cohort, 3 times larger than this study, observed a slightly higher incidence of baseline glottic stenosis at 4.5%.…”
Section: Discussioncontrasting
confidence: 59%
See 2 more Smart Citations
“…Outside of airway surgery, glottic stenosis does not appear to be common in the natural history of iSGS. Dion et al demonstrated that although 31.3% of a group of patients with an autoimmune etiology underlying their subglottic stenosis demonstrated concurrent posterior glottic stenosis, only one case of concurrent glottic stenosis was noted out of 45 (2.2%) patients with iSGS 9 . Our LWEP cohort, 3 times larger than this study, observed a slightly higher incidence of baseline glottic stenosis at 4.5%.…”
Section: Discussioncontrasting
confidence: 59%
“…Stenosis higher in the larynx may lead one to suspect a greater role for underlying inflammatory processes including granulomatosis with polyangiitis (GPA) and microscopic polyangiitis, which affect younger individuals and may involve the subglottic surface of the vocal folds 19 . It is also possible that the underlying etiology behind the four individuals with glottic involvement of their scar could later be classified as having an ANCA‐negative form of GPA 9 . However, currently none of these four patients nor any of the 209 other patients included in this study have demonstrated any physical exam findings or laboratory tests that would suggest this underlying disease process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One prior study described cricoarytenoid joint fixation and vocal cord immobility suggestive of glottic involvement in 20% of its GPA-associated SGS cohort; another described development of posterior glottic stenosis in 28% of their 14 patients with GPA-associated SGS. 18,48 Our study showed that 33% of patients with GPA-associated SGS had glottic involvement and a shorter dilation interval and were more likely to have the clinical complaint of dysphonia. Surprisingly, VRQOL scores did not differ between groups, which may be due to limited availability of data.…”
Section: Discussionmentioning
confidence: 72%
“…Hesitation remains regarding employing the LWE for iSGS, with concern for the potential of thermal injury from the CO 2 laser promoting a proximal increase in scar length and the development of glottic involvement, a pathophysiology observed infrequently within the natural history of iSGS. 19 Future studies should focus on the rate of complications within airway surgery-naı ¨ve patients with iSGS, looking for evidence of postoperative scar migration. While we acknowledge the short follow-up of some of our patients within this analysis, the median for the cohort overall was 5.6 years, approximately 4 times greater than the PCORI analysis (1.2 years).…”
Section: Next Steps and Limitationsmentioning
confidence: 99%